A report on the factors associated with productivity in selected Philippine communities - Minoza, Aurora A. ([S.l. s.n., 1976)
"The study attempted to determine the following: 1. The crucial inputs in agricultural productivity; 2. The factors which impede agricultural productivity; 3. The factors which facilitate agricultural productivity; 4. The socio-psychological variables associated with productivity."--Statement of the problem.
Includes tables and appendices.
Mimeographed.
U.P.-NSDB project no. 7301 So.
Keywords: Agriculture -- Economic aspects -- Philippines